UPAYA MENINGKATKAN KOSA KATA MELALUI METODE BERMAIN PERAN PADA ANAK TUNAGRAHITA RINGAN (PTK Kelas DV di SLB Kartini Batam) - Nurliya - Febrisma (Jurnal Penelitian Pendidikan Khusus, 2013)
This research is a classroom action research background by mild mental retardation children lack vocabulary. For intervention is using baermain role aims to enhance the vocabulary of children.